2018
DOI: 10.7567/jjap.57.08re10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cu addition to perovskite CH3NH3PbI3− x Cl x photovoltaic devices with hot airflow during spin-coating

Abstract: CH3NH3PbI3−xClx perovskite-based photovoltaic devices were fabricated by a spin-coating technique using hot airflow, and the effects of CuX (X = I, Br, or Cl) addition to perovskite precursor solutions on photovoltaic properties were investigated. Highly 100-oriented perovskite grains were formed using hot airflow during spin-coating. Compared with pristine perovskite CH3NH3PbI3−xClx crystals, grain sizes of the perovskite crystals decreased with the addition of CuBr or CuI, and the coverages of perovskite lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The doped Cl ions could lengthen the diffusion length of excitons, which resulted in the improvement in the conversion efficiency [26][27][28][29][30]. In addition, studies on metal atom doping, such as tin (Sn) [31,32], germanium [33,34], antimony (Sb) [35][36][37][38][39][40], copper (Cu) [41][42][43][44], arsenic (As) [45], or thallium (Tl) [34], at the lead (Pb) sites have been performed. The optical absorption ranges of the perovskite solar cells were expanded by Sn or Tl doping [31,32,34], and the photoconversion efficiencies were improved by Sb-, Cu-, or As doping.…”
Section: Introductionmentioning
confidence: 99%
“…The doped Cl ions could lengthen the diffusion length of excitons, which resulted in the improvement in the conversion efficiency [26][27][28][29][30]. In addition, studies on metal atom doping, such as tin (Sn) [31,32], germanium [33,34], antimony (Sb) [35][36][37][38][39][40], copper (Cu) [41][42][43][44], arsenic (As) [45], or thallium (Tl) [34], at the lead (Pb) sites have been performed. The optical absorption ranges of the perovskite solar cells were expanded by Sn or Tl doping [31,32,34], and the photoconversion efficiencies were improved by Sb-, Cu-, or As doping.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] In previous studies, it was reported that the addition of Cu compounds to perovskite precursor solutions in methylammonium (MA) and Cs-based perovskite solar cells contributed to increases in grain sizes and preferred crystal orientations, resulting in enhanced device properties. [9][10][11][12][13] These improvements in the film qualities of the perovskite compounds were attributed to the introduction of Cu, which delayed the growth rate of perovskite crystals. 14) Co-addition of Cu and alkali metals to MA-based perovskite has also been reported to enhance photovoltaic properties [15][16][17][18] or device stabilities.…”
Section: Introductionmentioning
confidence: 99%
“…The performances of photovoltaic devices are strongly dependent on the atomic structures and elemental compositions of the perovskite halide crystals [6,39,40]. Doping some elements such as tin (Sn) [41][42][43][44][45], antimony (Sb) [46][47][48], copper (Cu) [49][50][51][52][53][54][55], arsenic (As) [56], germanium (Ge) [57][58][59], zinc (Zn) [59][60][61][62], manganese (Mn) [63,64], yttrium (Y) [64], strontium (Sr) [65], indium (In) [58], cobalt (Co) [38,66], europium (Eu) [67], thallium (Tl) [58], or bismuth (Bi) [68] at the lead (Pb) site has been attempted and investigated. The photoconversion ranges of the per-ovskite devices have been expanded by introducing Sn or Tl [41,58].…”
Section: Introductionmentioning
confidence: 99%